Data Potensi dan Kontribusi Hasil Pertanian Di Jorong Dama Gadang, Nagari Dalko - Rino, Rino; Nurgita Fauziah; Diki Alfarizi; Arindy Indah Permata; Fauzan Rahman; Fharenza Halmaroza; Hayatin Puspa Dilah; Yaumil Akbar (Manaruko: Jurnal Pengabdian Masyarakat, 2024)
Globalization has brought significant changes in agricultural dynamics, the contribution of agriculture to rural communities in facing current global challenges, such as climate change, food security and environmental sustainability. This research was using a qualitative descriptive approach by collecting data through field observations, in-depth interviews with farmers, and literature analysis. The research results show that agriculture in Jorong Dama Gadang plays a crucial role in providing food for local and global communities, maintaining ecosystems, and adapting to climate change. Jorong Dama Gadang farmers have adopted sustainable farming practices, such as the use of organic fertilizer, crop rotation, and soil conservation, which helps reduce negative impacts on the environment. However, they also face major challenges, including limited access to technology and markets, and the intensifying impacts of climate change. This article suggests the need for policies that support rural agriculture through increased access to technology, education, and infrastructure investment to ensure their continued contribution to global challenges